Removal of elemental mercury using magnetic Fe-containing carbon prepared from sludge flocculated with ferrous sulfate by zinc chloride activation. (October 2021) - Wang, Yuan; Li, Honghu; Shao, Yan; Guo, Huajun; Liu, Zihao; Hu, Guofeng; Xiang, Hao; Hu, Jiangjun
Abstract: In this work, sewage sludge flocculated with ferrous sulfate (SFS) was treated by one-step pyrolysis and ZnCl2 activation to obtain magnetic Fe-containing carbon, which was used to remove elemental mercury (Hg 0 ) from flue gas. When 30% ZnCl2 was added to SFS (names as SFS-30), sulfides, chloride, magnetic Fex Oy, as well as a suitable BET surface area were produced during pyrolysis. SFS-30 showed a maximum mercury removal efficiency of 96.1%. The presence of O2 and a low SO2 concentration enhanced Hg 0 removal, while H2 O vapor and a high concentration of SO2 inhibited it. The addition of ZnCl2 increased the BET surface area as well as the conversion of sulfate to sulfide, which were both beneficial for Hg 0 removal. In addition, the generated magnetism during the pyrolysis process assisted in the recovery and utilization of SFS-30 in flue gas. After being magnetically separated from a mixture with fly ash, spent SFS-30 was thermally regenerated and recycled. After 8 Hg 0 capture and regeneration cycles, the removal efficiency was not notably degraded, demonstrating that SFS-30 prepared by one-step pyrolysis with ZnCl2 activation can be used for Hg 0 removal. The results of this study have guiding significance for practical engineering applications of this material. Graphical abstract: Image 1 Highlights: Sewage sludge flocculated with ferrous sulfate was utilized for Hg 0 removal. Magnetic sorbent was obtained by one-step pyrolysis and ZnCl2 activation. Multiple active sites (Fex Oy, sulfide and chloride) contributed to Hg 0 removal. The study has guiding significance for utilization of ferrous flocculated sludge.